Covering violence against women and girls on the border: Comparing news from Texas and Mexico - Mensa, Marta (2025)
This study investigates violence against women and girls (VAWG) along the Texas-Mexico border through the lens of the news published in newspapers: MyRGV in McAllen (Texas), the El Paso Times in El Paso (Texas), El Mañana de Reynosa in Tamaulipas (Mexico), and El Heraldo de Juárez in Ciudad Juárez (Mexico). It employs a mixed-method approach, conducting quantitative content analysis and qualitative framing analysis. The findings reveal that Mexican newspapers primarily chose to publish stories about murder as the main crime against women and girls, while Texas newspapers focused on sexual violence. Mexican newspapers also covered immigration-related VAWG. Female journalists in Mexico often connected crimes with psychological trauma. Texas newspapers employed episodic framing and victim-blaming, whereas Mexican newspapers framed stories in a victim-supporting manner. Texas newspapers did not distinguish crimes against women from other crimes, whereas Mexican newspapers used the term 'femicide' and treated crimes against women and children as gender- and age-specific.